2016
DOI: 10.1037/apl0000141
|View full text |Cite
|
Sign up to set email alerts
|

The problem of effect size heterogeneity in meta-analytic structural equation modeling.

Abstract: Scholars increasingly recognize the potential of meta-analytic structural equation modeling (MASEM) as a way to build and test theory (Bergh et al., 2016). Yet, 1 of the greatest challenges facing MASEM researchers is how to incorporate and model meaningful effect size heterogeneity identified in the bivariate meta-analysis into MASEM. Unfortunately, common MASEM approaches in applied psychology (i.e., Viswesvaran & Ones, 1995) fail to account for effect size heterogeneity. This means that MASEM effect sizes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
160
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(169 citation statements)
references
References 49 publications
1
160
0
Order By: Relevance
“…Many researchers have expressed concern that the presence of heterogeneity in the effect sizes may pose serious problems for MASEM (Sheng, Kong, Cortina, & Hou, ; Yu, Downes, Carter, & O'Boyle, ; Cheung, forthcoming). Particularly, as Murphy () claims, if between‐study heterogeneity exists, we cannot be confident that the observed correlation matrix input in MASEM reflects reality.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers have expressed concern that the presence of heterogeneity in the effect sizes may pose serious problems for MASEM (Sheng, Kong, Cortina, & Hou, ; Yu, Downes, Carter, & O'Boyle, ; Cheung, forthcoming). Particularly, as Murphy () claims, if between‐study heterogeneity exists, we cannot be confident that the observed correlation matrix input in MASEM reflects reality.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it is difficult to test moderator variables (Bergh et al, ). Fortunately, there is a rich literature emerging with suggestions how to handle these problems (Tang and Cheung, ; Yu et al, ).…”
Section: Meta‐analytic Structural Equation Modelling (Masem)mentioning
confidence: 99%
“…A related statistic, the I 2 value, indicates the ratio of true heterogeneity to sampling error: A value of 0 for the I 2 would indicate that variability is solely due to R e t r a c t e d sampling error (Huedo-Medina et al, 2006). To test our incremental validity hypothesis, we used meta-analytic regression procedures (e.g., Zhao et al, 2010) combined with fullinformation meta-analytic structural equation modelling (FIMASEM; Yu, Downes, Carter, & O'Boyle, 2016), a type of meta-analytic SEM (Viswesvaran & Ones, 1995) that uses SD q estimates to assess credibility intervals for model parameter estimates. 5 To test our mediation hypothesis, we used FIMASEM's (Yu et al, 2016) estimates of indirect effect parameters.…”
Section: Coding and Analytical Techniquesmentioning
confidence: 99%
“…To test our incremental validity hypothesis, we used meta-analytic regression procedures (e.g., Zhao et al, 2010) combined with fullinformation meta-analytic structural equation modelling (FIMASEM; Yu, Downes, Carter, & O'Boyle, 2016), a type of meta-analytic SEM (Viswesvaran & Ones, 1995) that uses SD q estimates to assess credibility intervals for model parameter estimates. 5 To test our mediation hypothesis, we used FIMASEM's (Yu et al, 2016) estimates of indirect effect parameters. Finally, we opted for a regression approach to test our moderators (Brinckmann et al, 2010;Geyskens et al, 2009).…”
Section: Coding and Analytical Techniquesmentioning
confidence: 99%
See 1 more Smart Citation